2020
DOI: 10.48550/arxiv.2004.02861
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chain breaking and Kosterlitz-Thouless scaling at the many-body localization transition in the random field Heisenberg spin chain

Nicolas Laflorencie,
Gabriel Lemarié,
Nicolas Macé

Abstract: Despite tremendous theoretical efforts to understand subtleties of the many-body localization (MBL) transition, many questions remain open, in particular concerning its critical properties.Here we make the key observation that MBL in one dimension is accompanied by a spin freezing mechanism which causes chain breakings in the thermodynamic limit. Using analytical and numerical approaches, we show that such chain breakings directly probe the typical localization length, and that their scaling properties at the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 103 publications
1
17
0
Order By: Relevance
“…More generally, the double-peak U-shape structure observed in Fig. 5 (b) in the disordered phase is also observed in the context of many-body localization at high energy, and is a fingerprint of ergodicity breaking [146][147][148][149][150]. In Fig.…”
Section: Real-space and Ergodicity Properties A Local Density Of Bosonssupporting
confidence: 61%
See 3 more Smart Citations
“…More generally, the double-peak U-shape structure observed in Fig. 5 (b) in the disordered phase is also observed in the context of many-body localization at high energy, and is a fingerprint of ergodicity breaking [146][147][148][149][150]. In Fig.…”
Section: Real-space and Ergodicity Properties A Local Density Of Bosonssupporting
confidence: 61%
“…The finite-size scaling analysis of localization transitions in graphs of effective infinite dimensionality such as the Cayley tree is particularly subtle. This was illustrated recently in the Anderson transition on random graphs [20,21,34], in the MBL transition [145,150] and in certain classes of random matrices [33,158,159]. The difficulty comes from the fact that the volume of the system N (the number of sites) varies exponentially with the linear size of the system, i.e., the number of generations G in the Cayley tree.…”
Section: A Scaling Analysis Across the Transitionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also showed that the numerical results from the earlier RGs are quite consistent with this scenario, even though they had been instead fit to one-parameter scaling. The conventional scaling assumptions used for exact calculations on small systems are also starting to be revisited [28,29]. In Ref.…”
Section: √ Ymentioning
confidence: 99%